2023
DOI: 10.18632/aging.204465
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the mechanism of Shaoyao-Gancao Decoction in the treatment of gastric carcinoma based on network pharmacology and experimental verification

Abstract: Background: Shaoyao-Gancao Decoction (SG-D) is a famous classical Chinese prescription that has been used in the treatment of numerous kinds of diseases. However, its mechanism of action in the treatment of Gastric carcinoma (GC) is not clear. Methods: The active ingredients and targets of SG-D were screened using network pharmacology, and GC-related targets were retrieved through several databases. The protein-protein interaction network was then further constructed and GO and KEGG enrichment analysis were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The above results indicated that EM combined with DDP could effectively inhibit the migration and invasion ability of MKN45/DDP cells. Apoptosis is involved in tumor development as a death mechanism regulated by multiple apoptotic genes [ 12 ]. Our in vitro experiments showed that the apoptosis rate of drug-resistant cells increased to varying degrees in each treatment group compared to the control group, with the highest rate observed in the combination group.…”
Section: Discussionmentioning
confidence: 99%
“…The above results indicated that EM combined with DDP could effectively inhibit the migration and invasion ability of MKN45/DDP cells. Apoptosis is involved in tumor development as a death mechanism regulated by multiple apoptotic genes [ 12 ]. Our in vitro experiments showed that the apoptosis rate of drug-resistant cells increased to varying degrees in each treatment group compared to the control group, with the highest rate observed in the combination group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 , 33 ] Lastly, Cytoscape software (version 3.9.1) was used to create the “THSWD-drug-active compound-intersection gene-hub gene-AVNFH” network diagram to illustrate the disease-drug interaction. [ 34 ]…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have used LC–MS to improve detection capabilities for traditional medicinal plant [ 9 , 10 ]. Network pharmacology is recognized for its cost-effectiveness in drug development and is a promising approach for studying compound–proteins/genes–disease pathways, such as the pharmacological mechanisms of traditional Chinese medicine [ 11 ]. This technique offers valuable insights into analysis of complex plant metabolites and Quality control.…”
Section: Introductionmentioning
confidence: 99%